Assessment of Soft Tissue Changes after Various Orthognathic Surgeries for Class III Correction of Cleft Lip and Cleft Palate Patients: A Systematic Review and Meta-Analysis - B Kanagasabapathy; Shubham Sharma; Piyush Dua; Nikil K. Jain; V Preethi; Monika (Journal of Pharmacy and Bioallied Sciences)
The study aimed to evaluate soft tissue changes resulting from orthognathic surgery, specifically LeFort osteotomy, and distraction osteogenesis, in individuals with cleft lip and palate (CLP) suffering from midface hypoplasia. Following PRISMA guidelines, eight papers met inclusion criteria, with six providing quantitative data for meta-analysis. Notably, significant improvements were observed in both hard and soft tissues, particularly with horizontal maxillary advancement. Overall, orthognathic surgery positively influenced soft tissue profiles, especially the combination of LeFort osteotomy and sagittal split osteotomy. Moreover, maxillary distraction osteogenesis demonstrated superior soft tissue changes compared to LeFort I osteotomy alone, suggesting avenues for further research and potential enhancements.